Association between Domestic Violence and School Violence: a preliminary analysis - Lúcia Cavalcanti de Albuquerque Williams; Ana Carina Stelko Pereira (Educação: Teoria e Prática, 2008)
Usually, one investigates marital violence, children victimization, and school violence in an isolated way. The aim of this paper is to highlight the relationship between domestic violence and school violence, suggesting actions to deal with these serious issues. With this goal in mind, two studies are described in this paper. The first one evaluates if boys who behave aggressively in school, in comparison with their non-aggressive peers, have more incidence of domestic violence exposure and victimization. The second study investigates if exposure to domestic violence and child victimization are factors associated with bullying. These studies indicated that there is a relation between the violence experienced in these two contexts; however they emphasize the need for further investigations with more participant and longitudinal studies. Teacher in-service training is suggested, aimed at: identifying students living in families with a history of domestic violence; supporting teachers and principals in case of disclosures in the school setting; social skills training for students; class discussions about healthy and non-violent family relationships and, psychotherapy referral to students who are victimized.